The Organization for Economic Cooperation and Development (OECD) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The Organization for Economic Cooperation and Development (OECD)The Organization for Economic Cooperation and Development is one of the international bodies set up by the West after World War II. It is responsible for analysing and assessing the...